The Dilemma Whether to Produce Glued or Sawn Wooden Beams? - Michal Zeman (University of Zagreb, Faculty of Forestry and Wood Technology, 2013)
This article gives an overview of the contemporary development of wood production in the Czech Republic with the focus on the production of static structural members. This issue refers to literary sources of several authors dealing with the history and development of sawmills and adaptations of production strategies to the current trends. The study is based on information collected and assessed during the sawmill operations used by wood processing companies to make strategic decisions. Interaction of these input data and information acquired from the available literature indicates the possibility of development and specialization of the existing sawmills in upcoming years. Nearly 20 per cent of round timber is processed into static structural members, wooden beams. Considering the rising prices of input raw material, the question of the extent of cost-effectiveness and economy of sawn structural members arises. This article is aimed to clarify the seissues and compare the production costs of sawn and glued structural members used in common wooden constructions, such as roof frames, prefabricated houses, etc. This may have an impact not only on sawmills but also on the extent of use of this type of wooden construction products. The question is whether the new restructuring of sawmills is coming or not?